A psychogeriatric survey of old people's homes. Issue 6302 (14th November 1981) - Clarke, M G; Williams, A J; Jones, P A
Abstract : An assessment of mental impairment and behavioral disabilities in 289 residents in six old people's homes indicated that 50.6% were probably demented and 54% needed considerable help in daily living, 74% were taking prescribed medication, and 11% were taking four or more prescribed drugs. There was a wide variation between homes in those rated as behaviourally disabled, and in the amount of medication prescribed. A follow-up of 60 mentally impaired residents showed few remediable psychiatric disorders or psychotoxic drug effects. A community psychiatric nurse working with the psychogeriatric team would provide a useful support service to old people's homes, particularly where there is a high proportion of disturbed residents and where the staff lack nursing experience.